PENGARUH PERTUMBUHAN EKONOMI TERHADAP INDEKS PEMBANGUNAN MANUSIA DI KOTA PEKANBARU - Herman, Herman (Sekolah Tinggi Ilmu Ekonomi Riau, 2017)
The purpose of this research is to know how big influence of economic growth to index of human development in Pekanbaru. The method used in this paper is the study of literature supported by quantitative descriptive analysis of secondary data. namely data development of HDI, districts / cities and economic growth rate in 2006-2016 BPS Pekanbaru. statistical test used is simple linear regression, tes_t, and coefficient of determination. Tests conducted to determine the relationship between independent variables and dependent variables. Based on the research, it is found that economic growth has a significant negative effect on human development index. and the magnitude of the effect of economic growth variables on the human development index by 69.9 percent